Analysis Application of GMP, SSOP, GTP And The Potential For Business Development - Bhiaztika Ristyanadi; Susinggih Wijana; Wignyanto Wignyanto (Wacana Journal of Social and Humanity Studies, 2014)
Establishing crab meat canning industry which has several units production scattered in Madura region. A unit production is assigned to provide canning raw material requirements such as strip crab meat. This study aims to analyze problems of the company to know defense strategy and how to increase productivity. Further more, evaluating quality management system activities aims to improve the system and product quality to conform to the wishes of consumers. Improvement of product quality conducted an assessment of the quality management system which applied to unit production using the scoring method. This assessment aims to reduce the risk of production failure, with prevent infringement of production processes. Assessment of the production aspects including GMP, GTP and SSOP. Then to identify problems and analyze what strategies will be used can used a SWOT analysis. Analysis strategy using SWOT method aims to determine what factors can affect company productivity. Observation result of GMP overall implementation on unit process did not implemented properly. Average total percentage earned was only 50% which means GMP implementation didnt meet eligibility standarts. While the GTP application only obtained between 25% to 50%. That percentage result indicates that the implementation of the GTP did meet the standards. It is also found in the SSOP observation which indicates average percentage result was only 25% to 50%. While the results of the SWOT analysis namely the company improvement strategy which is used to improve productivity. It can be done by increasing the number of partnerships, increasing supply of raw materials and improving product quality. Keywords: Quality Management System, Quality, SWOT